Association of Preoperative Growth Differentiation Factor-15 Concentrations and Postoperative Cardiovascular Events after Major Noncardiac Surgery. (11th April 2023) - Duceppe, Emmanuelle; Borges, Flavia K.; Conen, David; Tiboni, Maria; Chan, Matthew T. V.; Patel, Ameen; Sessler, Daniel I.; Kavsak, Peter A.; Ofori, Sandra; Srinathan, Sadeesh; Pearse, Rupert; Jaffe, Allan S.; et al.
Abstract : Background: The association between growth differentiation factor-15 concentrations and cardiovascular disease has been well described. The study hypothesis was that growth differentiation factor-15 may help cardiac risk stratification in noncardiac surgical patients, in addition to clinical evaluation. Methods: The objective of the study was to determine whether preoperative serum growth differentiation factor-15 is associated with the composite primary outcome of myocardial injury after noncardiac surgery and vascular death at 30 days and can improve cardiac risk prediction in noncardiac surgery. This is a prospective cohort study of patients 45 yr or older having major noncardiac surgery. The association between preoperative growth differentiation factor-15 and the primary outcome was determined after adjusting for the Revised Cardiac Risk Index. Preoperative N-terminal-pro hormone brain natriuretic peptide was also added to compare predictive performance with growth differentiation factor-15. Results: Between October 27, 2008, and October 30, 2013, a total of 5, 238 patients were included who had preoperative growth differentiation factor-15 measured (median, 1, 325; interquartile range, 880 to 2, 132 pg/ml). The risk of myocardial injury after noncardiac surgery and vascular death was 99 of 1, 705 (5.8%) for growth differentiation factor-15 less than 1, 000 pg/ml, 161 of 1, 332 (12.1%) for growth differentiation factor-15 1, 000 to less than 1, 500 pg/ml, 302 of 1476 (20.5%) for growth differentiation factor-15 1, 500 to less than 3, 000 pg/ml, and 247 of 725 (34.1%) for growth differentiation factor-15 concentrations 3, 000 pg/ml or greater. Compared to patients who had growth differentiation factor-15 concentrations less than 1, 000 pg/ml, the corresponding adjusted hazard ratio for each growth differentiation factor-15 category was 1.93 (95% CI, 1.50 to 2.48), 3.04 (95% CI, 2.41 to 3.84), and 4.8 (95% CI, 3.76 to 6.14), respectively. The addition of growth differentiation factor-15 improved cardiac risk classification by 30.1% (301 per 1, 000 patients) compared to Revised Cardiac Risk Index alone. It also provided additional risk classification beyond the combination of preoperative N-terminal-pro hormone brain natriuretic peptide and Revised Cardiac Risk Index (16.1%; 161 per 1, 000 patients). Conclusions: Growth differentiation factor-15 is strongly associated with 30-day risk of major cardiovascular events and significantly improved cardiac risk prediction in patients undergoing noncardiac surgery. Abstract : This study used clinical data and serum samples from 5, 238 patients enrolled in a multisite cohort study (Vascular Events in Noncardiac Surgery Evaluation study; VISION). The authors assessed the association between increased preoperative serum growth differentiation factor-15 and the primary study outcome of 30-day risk of myocardial injury after noncardiac surgery and vascular death. A preoperative growth differentiation factor-15 concentration 1, 500 pg/ml or greater was associated with a 24.9% risk of myocardial injury after noncardiac surgery and vascular death. In the subset of patients who had preoperative N-terminal-pro hormone brain natriuretic peptide results available (n = 4, 246), the incidence of myocardial injury after noncardiac surgery and vascular death was 606 patients (14.3%). In a multivariable model that included preoperative Revised Cardiac Risk Index score and preoperative N-terminal-pro hormone brain natriuretic peptide categories, both preoperative growth differentiation factor-15 and N-terminal-pro hormone brain natriuretic peptide remained independently associated with myocardial injury after noncardiac surgery and vascular death and vascular mortality at 30 days.